The psychosocial outcomes of anoxic brain injury following cardiac arrest - Wilson, Michelle; Staniforth, Andrew; Till, Richard; das Nair, Roshan; Vesey, Patrick (Elsevier, 2014)
Aim of the study: This exploratory study aimed to investigate the psychosocial outcomes for cardiac arrest survivors and explore if there is a greater impact on psychosocial outcome for individuals experiencing anoxic brain injury as a result of the cardiac arrest.